Approaching the end of post - soviet transition? Trends of youth crime in Klaipėda in 2005-2019 - Liutauras Kraniauskas; Arūnas Acus (Social Welfare: Interdisciplinary Approach)
The article presents a sociological and criminological analysis of data on registered youth criminal offences (young people of 14-29 years old) in Klaipėda. The analysed period covers the years from 2005 to 2019 (late post-Soviet period).  It includes youth crime offences and persons suspected of committing a crime. The period is characterised by a constant downward trend in crime. There were no substantial changes in criminal law during this period, however, Lithuania significantly strengthened the legal and material background for work with juveniles and young adults.  On the basis of the insights of the theories of anomie, social control and ecological criminology, the article analyses the key indicators of youth crime and its dynamics. The changes by age and employment of persons who have allegedly committed criminal offences are analysed.